A Low Strain A‐Site Deficient Perovskite Lithium Lanthanum Niobate Anode for Superior Li+ Storage. (1st October 2021) - Xiong, Xuhui; Yang, Liting; Liang, Guisheng; Wang, Chao; Chen, Guanyu; Yang, Ziqi; Che, Renchao
Abstract: The oxide perovskite family holds great promise for diverse applications on account of their unique chemical and physical properties. However, owing to the inadequate Li + ‐storage sites, the insertion‐type perovskite anodes for lithium‐ion batteries (LIBs) are limited. A‐site deficient perovskites with rich intrinsic vacancies and ion transport channels are believed to be the desirable hosts of superior Li + storage. Herein, the perovskite Li0.1 La0.3 NbO3 (LLNO) is designed and demonstrated as the remarkable anode for LIBs with a high specific capacity, a safe operating voltage, an excellent rate performance, and a long cycling life. More importantly, the outstanding cycling stability of LLNO is originated from its low strain characteristic with a maximum volume change of only 1.17%. The exceptional rate performance can be explained by the unconventional Li + transport pathways with external → grain boundaries → lattice deficiencies. These results not only reveal that A‐site deficient perovskite LLNO is a promising anode for LIBs but also provide fundamental insights into the Li + ions transport mechanism, facilitating the development of high‐performance perovskite anodes. Abstract : A‐site deficient perovskite Li0.1 La0.3 NbO3 is designed as the anode for Li + storage, exhibiting high reversible capacity, safe operating potential, excellent rate, and cycling performance. The maximum volume change is only 1.17%, showing a low strain characteristic. The fast Li + transport pathways with external → grain boundaries → lattice deficiencies are demonstrated, which leads to excellent electrochemical performance.